2013
DOI: 10.1074/jbc.m112.387076
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between αvβ3 Integrin and Nucleolin Regulates Human Endothelial and Glioma Cell Migration

Abstract: Background: Cell surface nucleolin (NCL) is a promising target for development of anticancer agents. Results: A novel pathway that includes ␣ ␤ 3 integrin and leads to cell surface NCL localization and cell migration has been identified. Conclusion: ␣ ␤ 3 can be used as a biomarker for the use of NCL antagonists. Significance: This pathway is active in endothelial and glioma cells, as well as in human glioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 60 publications
8
58
1
5
Order By: Relevance
“…It has also been shown that cell surface nucleolin is implicated in the migration of endothelial and glioma cells (Koutsioumpa et al, 2013). Our results clearly indicate that the knockdown of nucleolin markedly attenuates the spreading and migration of A375 cells on fibronectin, suggesting a key role of lipid raft-dependent β1 integrin-nucleolin interaction in cell migration on fibronectin.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…It has also been shown that cell surface nucleolin is implicated in the migration of endothelial and glioma cells (Koutsioumpa et al, 2013). Our results clearly indicate that the knockdown of nucleolin markedly attenuates the spreading and migration of A375 cells on fibronectin, suggesting a key role of lipid raft-dependent β1 integrin-nucleolin interaction in cell migration on fibronectin.…”
Section: Discussionsupporting
confidence: 65%
“…For example, Kang et al (2009) reported that although only partially colocalized, αvβ3 integrin and nucleolin protein are highly coexpressed in HeLa cells. Interestingly, Koutsioumpa et al (2013) recently indicated that the interplay between αvβ3 integrin and nucleolin regulates human endothelial and glioma cell migration. Reyes-Reyes and Akiyama (2008) have also shown the important role of surface nucleolin in p-selectin-mediated α5β1 integrin activation and colo-320 cell adhesion on fibronectin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, NCL enhances translation of many mRNA encoding for oncogenic proteins [42]. Cell surface NCL has been reported to act as a receptor for several growth factor such as midkine [43] and pleiotrophin [43][44][45] involved in angiogenesis and tumor growth, hepatocyte growth factor (HGF) involved in the mechanisms of metastasis and cell adhesion [46] and P-selectin that induces signaling pathways of cell adhesion and invasion [47]. In addition, the implication of cell surface NCL in proliferative diseases may be related to the fact that it exists in a protein complex of 500-kDa, including several proteins involved in cancer progression.…”
Section: Ncl: a Promising Target For Cancer Therapymentioning
confidence: 99%